The Relationship between Cognitive Development in the Concrete Operational Stage and Mathematical Problem Solving Abilities in Grade 4 Children at SDN Podorejo 1 - Aryan Hasna Haniah; Krisna Immanuel; Aulia Azzahra; Linda Zuli Andini (Education Generation Journal, 2023)
This research is motivated by the importance of mathematical problem solving abilities, which also include stages in cognitive development according to Jean Piaget. This research aims to determine the relationship between concrete operational stage cognitive development and mathematical problem solving abilities in grade 4 children at SDN Podorejo 1. The subjects of this research were grade 4, totaling 14 students. The data collection techniques used are documentation, observation, and testing. The results of this research show that there is a relationship between cognitive development at the concrete operational stage and mathematical problem solving abilities in grade 4 children at SDN Podorejo 1. The conclusion of this research is that there is a relationship between problem solving ability and cognitive development at the concrete operational stage. 2. This research aims to apply and explain geometry material to students at SDN Podorejo 1, especially on cube geometric material.